Solution-Derived, Chloride-Containing Minerals as a Waste Form for Alkali Chlorides - Riley, Brian J.; Crum, Jarrod V.; Matyáš, Josef; McCloy, John S.; Lepry, William C. (Journal of the American Ceramic Society, 2012)
Sodalite (Na8(AlSiO4)6Cl2) and cancrinite ((Na,K)6Ca2(AlSiO4)6Cl4) are environmentally stable, chloride‐containing minerals that are a logical waste form option for the mixed alkali chloride salt waste stream that is generated from a proposed electrochemical separations process during nuclear fuel reprocessing. Here, we discuss a low‐temperature, solution‐based process to make these phases where sodalite particles are produced in the form of a fine powder with particle sizes on the order of 1–10 μm. Due to the small particle size, these powders require additional treatment to form a monolith. In this study, the powders were pressed into pellets and fired to achieve >90% of the theoretical density of sodalite (2.27 × 10−3 kg/m3). The cancrinite structure, identified as the best candidate mineral form in terms of waste loading capacity, was only produced on a limited basis but was converted to sodalite upon firing. Here, we discuss the specifics of the solution‐based approach, the chemical durability of select waste forms as well as the steps taken to maximize the chloride‐containing phases, decrease chloride loss during pellet firing, and to increase pellet densities.